A Calming Cushion as a Therapeutic Wellness Tool for Youths with Disabilities and History of Trauma. Issue 4 (28th July 2017) - Polak, Reizel; Hutchinson, Dori; Perryman, Louise; Brueck, Stephanie
Abstract: Seclusion and restraint are commonly used by residential staff to control unsafe behaviors of youths with disabilities and complex trauma histories. This pilot study examined the effect of a nonrestraining cushion as a calming device and wellness tool in a setting that prohibits supportive physical contact, to see to what extent the cushion might help these youths to better regulate their emotional distress and unwanted behaviors. Volunteers used the cushion for 15 minutes over 24 sessions. Nine students completed the study and reported reduction in anxiety and agitation, and a soothing feeling with residual effects to their daily routines. This pilot study suggests that the use of a nonrestraining, deep-pressure cushion may simulate a secure holding effect for young people with emotional dysregulation. The cushion is a safe and healing wellness tool that empowers youths and provides programs with an alternative to seclusion and restraint.